A rare case of acrochordon of external auditory canal - Gowda, Chandre Gowda Bendiganahalli Venkate; Kamath, Rakshita R. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Independently arising acrochordon of the external auditory canal is a rare entity with only one reported case in literature. We present here the second such case. A 54-yr old lady presented to our outpatient department with complains of aural fullness and reduced hearing in right ear for 2 weeks. Clinical examination showed a pedunculated polypoidal growth in the external auditory canal. Excisional biopsy and histopathology revealed an acrochordon. Following the procedure, patient was free of symptoms and all structures of the right ear were normal. In the head and neck region, acrochordons have only but once been reported in the external auditory canal and hence should be considered as a differential diagnosis in the masses of this region. Resection must be done for confirmation of diagnosis, differentiation from neoplasia and alleviation of symptoms when associated.